Peran Penambahan Misoprostol pada Penatalaksanaan Aktif Kala Tiga dalam Menurunkan Perdarahan Pasca Persalinan - Geni, Puti Lenggo; Rachman, Irwan Taufiqur; Pradjatmo, Heru (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2017)
Background: Postpartum haemorrhage is the leading cause of maternal mortality in both developed and developing countries, which is almost 80 % due to the failure of the uterus to contract. Misoprostol is a powerful uterotonic agent used as an alternative in preventing postpartum haemorrhage.Objective: The purpose of this study was to determine whether administration of misoprostol adjunctive therapy in active management of the third stage of labor influenced postpartum blood loss.Method: This study was a non-blinding randomized controlled trial that divided subjects into two groups. The treatment group was the group who received misoprostol 600 mcg orally for adjunctive treatment in active management of the third stage of labor and the control group did not receive misoprostol, each group also got routine oxytocin 10 IU intramuscularly. Both group were assessed of the number of blood loss in the fourth stage of labor, decreased levels of hemoglobin and hematocrit within 24 hours after delivery. Chi square test was conducted to determine the strength of the relationship between the two groups.Result and Discussion: The study recruited 104 subjects, there were significant difference for the mean number of blood loss in the fourth stage of labor and the decrease in hemoglobin levels within 24 hours of postpartum between treatment and control group (OR 2.45; 95% CI 1.05-5.71, p=0.04), (OR 2.99; 95% CI 1.26-7.11, p=0.01). The mean of the decreasing hematocrit levels was statistically not significant between the two groups (OR 0.87; 95% CI 0.38-1.99, p=0.75).Conclusion: The addition of misoprostol to the routine active management of the third stage of labor was statistically significant to decrease amount of postpartum blood loss.Keywords: misoprostol, active management of the third stage of labor, postpartum blood loss, postpartum hemorrhage.